Digitalisasi Manajemen Keuangan UMKM Konveksi Aura Garmindo: Studi Kasus KKN Tematik di Desa Wonorejo, Demak - Muhammad Ghozali; Yunita Putri; Ratu Dentawyanjana; Risky Adi Saputra; Des Winta Fitri Sabila; Wifaqul Azmi, Minanul Muna; Minanul Muna; Susanti Wahyuningsih (STIE Pelita Nusantara, 2026)
The Thematic Community Service Program (Kuliah Kerja Nyata / KKN) with the theme of Independent Entrepreneurship was conducted in Wonorejo Village, Guntur District, Demak Regency, focusing on assisting the MSME (Micro, Small, and Medium Enterprise) Aura Garmindo Convection. This MSME faced several challenges, including unsystematic financial recording, limited marketing reach, labor shortages, and the absence of business location digitalization. The implementation methods included observation, interviews, mentoring, and the execution of digital-based programs. The main programs carried out consisted of digitalizing financial management through an Excel-based cash flow application, creating social media accounts for digital marketing, designing job vacancy posters, and registering the business location on Google Maps. The results of the program indicate an improvement in financial literacy, the establishment of a simple cash flow recording system, increased business visibility through social media, and easier digital access to the business location. The conclusion of this activity is that business digitalization can support the independence of MSMEs and enhance the sustainability of local businesses. The recommendation provided is the need for continuous assistance and consistency in implementing digitalization to ensure sustainable benefits. Keywords: thematic KKN, MSMEs, financial digitalization, digital marketing, independent entrepreneurship